2021
DOI: 10.3390/ijms22073786
|View full text |Cite
|
Sign up to set email alerts
|

Hemi- and Homozygous Loss-of-Function Mutations in DSG2 (Desmoglein-2) Cause Recessive Arrhythmogenic Cardiomyopathy with an Early Onset

Abstract: About 50% of patients with arrhythmogenic cardiomyopathy (ACM) carry a pathogenic or likely pathogenic mutation in the desmosomal genes. However, there is a significant number of patients without positive familial anamnesis. Therefore, the molecular reasons for ACM in these patients are frequently unknown and a genetic contribution might be underestimated. Here, we used a next-generation sequencing (NGS) approach and in addition single nucleotide polymor-phism (SNP) arrays for the genetic analysis of two indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 59 publications
1
22
0
2
Order By: Relevance
“…In ACM, loss of function due to NMD and triggered by PTC codon variants has been widely supported for all five desmosomal genes [ 9 , 21 , 26 , 27 , 28 , 29 ]. The position of a truncating mutation can govern the resulting phenotype, as mutations in the last exon can evade NMD [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In ACM, loss of function due to NMD and triggered by PTC codon variants has been widely supported for all five desmosomal genes [ 9 , 21 , 26 , 27 , 28 , 29 ]. The position of a truncating mutation can govern the resulting phenotype, as mutations in the last exon can evade NMD [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of function mutations in DSG2 affect cardiomyocyte cohesion, force transduction, and calcium processing [27]. Of note, a large number of studies have shown an association of mutations in DSG2 and arrhythmogenic right ventricular cardiomyopathy (ARVC) [21,28,29]. However, other studies proved the relationship between the development of DCM and mutations in DSG2 [11,30].…”
Section: Discussionmentioning
confidence: 99%
“…However, incomplete penetrance and variable expressivity ranging from mild phenotypes to severe cases including SCD are frequently observed even within the same family. In addition, de novo mutations and recessive, compound heterozygous, and digenetic inheritance can hide the genetic etiology in isolated index patients without familial history [18,19]. Currently, mutations in more than 25 different genes have been described (for an overview, see Fig.…”
Section: Genetic Causes and Modifiersmentioning
confidence: 99%
“…Plakophilin-2 and plakoglobin bind to the cytoplasmic domains of desmoglein-2 (DSG2) and desmocollin-2 (DSC2), which are type I transmembrane proteins from the cadherin family. Hetero-and homo-or compound heterozygous pathogenic mutations in DSG2 and DSC2 have been described in about 5% of ACM patients [19,[32][33][34]. The majority of DSG2 and DSC2 mutations are localized in the extracellular domains, which consist of four cadherin and an anker domain, carrying several N-glycosylations and O-mannosylations [35,36].…”
Section: Junctional Gene Mutationsmentioning
confidence: 99%